Napping in high-performance athletes: Sleepiness or sleepability?. Issue 3 (4th March 2021) - Gupta, Luke; Morgan, Kevin; North, Courtney; Gilchrist, Sarah
Abstract: Daytime napping is a common practice in high-performance athletes, and is widely assumed to reflect sleepiness arising from sports-related sleep debt. The possibility that athlete naps may also be indicative of 'sleepability', a capacity to nap on demand that is only weakly related to homeostatic sleep pressure, has not previously been tested. The present study compared daytime sleep latencies in high-performance athletes and non-athlete controls using a single nap opportunity model. Elite ( n  = 10), and sub-elite ( n  = 10) athletes, and non-athlete controls ( n  = 10) attended the laboratory for a first adaption trial, and a subsequent experimental trial. Subjective sleepiness was assessed using the Karolinska Sleepiness Scale (KSS) at 14:00, 14:30 and immediately prior to a 20-minute nap opportunity at 15:00. Sleep latencies were measured using polysomnography, and defined as the time from lights out to the first epoch of any stage of sleep (N1, N2, N3, REM). In unadjusted comparisons with non-athlete controls, elite athletes showed significantly shorter sleep latencies in both the adaptation ( p  < 0.05) and experimental trials ( p  < 0.05). These significant differences were maintained in models controlling for pre-trial KSS scores and pre-trial total sleep time (all p  < 0.05). Sleep latency scores for sub-elite athletes showed similar trends, but were more labile. These results are consistent with a conclusion that, among elite athletes, napping behaviour can reflect sleepability and may not necessarily result from nocturnal sleep disruption and daytime sleepiness.